Faktor-Faktor Yang Mempengaruhi Kinerja Pengawai Pengelola Keuangan: Sarana Pendukung Sistem Informasi Akuntansi, Sistem Pengendalian Intern Pemerintah Dan Budaya Organisasi - Silmi Kafah Aulia; Cris Kuntadi; Rachmat Pramukty (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that influence the Performance of Financial Managers, namely Supporting Facilities for Accounting Information Systems, Government Internal Control Systems and Organizational Culture, a literature study of accounting information systems. The purpose of writing this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) Accounting Information System Support Facilities affect the Performance of Financial Management Supervisors; 2) The Government's Internal Control System affects the Performance of Financial Management Supervisors; and 3) Organizational Culture influences the Performance of Financial Management Supervisors.